ECTHR_COMMITTEE 32208/22 vom 7. April 2026 , AFFAIRE I.M. c. ROUMANIE - Ecthr Committee (2026)
Violation de l'article 5 - Droit à la liberté et à la sûreté (Article 5-1 - Arrestation ou détention régulières;Article 5-1-e - Aliéné); Violation: 5;5-1;5-1-e